AL QAEDA TERRORISM IN THE ISLAMIC MAGHREB (AQIM): AN EXAMPLE OF SURVIVAL AND ADAPTABILITY - Echeverría, Carlos (Journal of the Spanish Institute for Strategic Studies, 2018)
In this article we examine how Al Qaeda in the Islamic Maghreb(AQIM) has transformed itself over recent years into one of the mostdynamic and productive parts -in terrorist terms- of Al Qaeda ‘Central’.Exploiting the comparative advantage offered by the Sahel strip,in autumn 2012 AQIM was one of the major culprits for the deterioratingsituation in the region. Its importance is demonstrated by itsgeographic scope, its terrorist attacks, its skill with propaganda and itssignificant terrorist financing activity. This is confirmed by its strategicstrength in the north of Mali and its ties of all kinds with the highlyactive Nigerian terrorist group Boko Haram.